Uyghur Legitimation and the Role of Buddhism - Kasai, Yukiyo (Dynamics in the history of religions, 2020)
From the 8th to the 14th century, Uyghurs experienced various changes in connection with the legitimation strageties of their rulers. The shift from their traditional religious beliefs to Manichaeism and then further to Buddhism, strongly influenced the presentation of the rulers’ power. This chapter discusses changes to Uyghur rulers’ legitimation strategies during this period is discussed.